1976
DOI: 10.1002/1097-0142(197612)38:6<2328::aid-cncr2820380620>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoid of the uterine cervix.Additional observations on a new tumor entity

Abstract: Twelve carcinoid tumors of the uterine cervix were studied. Based on the microscopic structure, they were divided into well-differentiated a n d poorly differentiated types. Both tumor varieties affected adult women. The clinical and gross features of these tumors were indistinguishable from those of invasive squamous cell carcinoma. Of the 12 patients, six died, four with poorly differentiated carcinoid and two with the well-differentiated type. Three patients are alive and symptom-free 9 months to 2 years af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
1
5

Year Published

1978
1978
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(42 citation statements)
references
References 29 publications
0
36
1
5
Order By: Relevance
“…Neuroendocrine carcinomas of the cervix have been classified into four distinct histologic types: small cell, large cell and carcinoid (typical and atypical) [4]. Primary cervical carcinoid tumor are exceedingly rare but typically behave more like welldifferentiated tumors and will not be addressed here.…”
Section: Diagnosis Pathology and Molecular Alterationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroendocrine carcinomas of the cervix have been classified into four distinct histologic types: small cell, large cell and carcinoid (typical and atypical) [4]. Primary cervical carcinoid tumor are exceedingly rare but typically behave more like welldifferentiated tumors and will not be addressed here.…”
Section: Diagnosis Pathology and Molecular Alterationsmentioning
confidence: 99%
“…One percent of all cervical cancer is of neuroendocrine histology, and there are approximately 100-200 cases diagnosed annually in the USA [4][5][6][7]. Given the rare nature of this disease, the vast majority of research investigating prognostic factors and optimal treatment is retrospective and based on relatively small case series.…”
Section: Introductionmentioning
confidence: 99%
“…In 1976, Albores-Saavedra et al [1] reported 12 cases of neuroendocrine tumors (NETs) arising in the uterine cervix and designated them as carcinoid tumors of the cervix. Thereafter, these tumors were further classified to 2 categories, small cell carcinoma and carcinoid tumor.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Because ASCC is a rare cervical tumor, accounting for only 1.5 to 5% of all cervical tumors, [1][2][3][4][5][6][7] most reports on ASCC have been concerned with one or a few cases. Therefore, development of in vivo and in vitro experimental systems is desirable not only for examining the biological behavior of ASCC, but also for establishing an effective clinical treatment.…”
mentioning
confidence: 99%
“…[8][9][10] In our previous studies, we found that TC-YIK cells retained the histochemical characteristics of ASCC cells and could be used as an in vitro experimental model of ASCC, and that the TC-YIK cells were possibly of neuroendocrine origin, based on electron microscopic evidence of small, electron-dense, membrane-bound neurosecretory-type granules and immunohistochemical evidence of neuron-specific enolase, chromogranin, serotonin and gastrin. 8,9,11) In terms of the origin of ASCC, however, there have been three theories: ASCC originates from (i) amine precursor uptake and decarboxylation (APUD) cells, 2,3,12) (ii) undifferentiated epithelial cells with multi-differentiation ability, 13) or (iii) stem cells. 7) In this study, to investigate the origin of ASCC of the uterine cervix and the feasibility of treatment of the tumor with a differentiation inducer, we examined the influence of dibutyryl cyclic adenosine 3′,5′-monophosphate (dBcAMP), a known differentiation inducer, on the characteristics of an ASCC cell line, TC-YIK.…”
mentioning
confidence: 99%